Analisis Kualitas Air Depot Air Minum Isi Ulang Kecamatan Geragai - Kalsum, Siti Umi; Kurniawan, Dwi; Setiadi, Mohd Rizqi; Marolop, Guntar; Suzana, Asih (Universitas Batanghari Jambi, 2025)
This study analyzes the quality of raw water and production water in refillable drinking water in Geragai District, East Tanjung Jabung Regency to see the feasibility of refillable drinking water in accordance with Minister of Health Regulation No. 2 of 2023 concerning Environmental Health. Sampling using total sampling techniques and laboratory analysis of samples measured in terms of physical, chemical and biological parameters in accordance with the Indonesian national standard method (SNI). Based on the results of physical tests, namely Total Dissolve Solid (TDS), it shows that the test results meet quality standards according to applicable regulations. The results of chemical tests show that there are two parameters that do not meet the requirements in raw water, namely Iron (Fe) and Manganese (Mn). Fe concentrations ranged from 2.71-3.09 mg/L with a quality standard of 0.2 mg/L and Mn concentrations ranged from 0.046-0.108 mg/L with a quality standard of 0.1 mg/L. While other chemical parameters hardness meet the established requirements. The results of microbiology laboratory tests showed that all samples contained coliform bacteria with concentrations between 1.6-7.8 per 100 ml in raw water and 3-15 per 100 ml in production water with the required quality standard of 0 per 100 ml. The results showed that refillable drinking water in Geragai sub-district needs to be monitored by the local health office and regular cleaning for depot owners.